Ð’Ð»Ð¸ÑÐ½Ð¸Ðµ Ñ‚Ñ€Ð¸Ñ„Ñ‚Ð¾Ñ€Ð¿ÐµÑ€Ð°Ð·Ð¸Ð½Ð° Ð¸ Ð´Ð¾Ð´ÐµÑ†Ð¸Ð»-Î²,D-Ð¼Ð°Ð»ÑŒÑ‚Ð¾Ð·Ð¸Ð´Ð° Ð½Ð° Ð³Ð¸Ð¿ÐµÑ€Ñ‚Ð¾Ð½Ð¸Ñ‡ÐµÑÐºÐ¸Ð¹ ÑÑ‚Ñ€ÐµÑÑ ÑÑ€Ð¸Ñ‚Ñ€Ð¾Ñ†Ð¸Ñ‚Ð¾Ð² Ð¼Ð»ÐµÐºÐ¾Ð¿Ð¸Ñ‚Ð°ÑŽÑ‰Ð¸Ñ… - Yershova, Natalia A.; Nipot, Elena E.; Shpakova, Natalia M.; Yershov, Sergey S.; Orlova, Natalia V. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2014)
The effect of dodecyl-Î²,D-maltoside (DM) and trifluoperazine (TFP) on mammalian (human, bovine, equine, rabbit)erythrocyte sensitivity to hypertonic stress (HS) (4.0 mol/l NaCl) was studied in this work. The use of amphiphilic compounds in the certain concentrations was demonstrated as resulting in an increased resistance to HS of human, bovine, equine erythrocytes, but not rabbit ones. Protective effect of amphiphilic compounds is higher at 37Â°C than at 0Â°C. Cationic TFP is more efficient than non-ionic DM. The substances under study were established as not affecting the potassium cation release out of cells under HS. Protective mechanism of TFP and DM is suggested as associated with their perturbating action on a membrane and prevention of transmembrane defect development up to hemolytic pore size.Probl Cryobiol Cryomed 2014; 24(3):231-237.